In vitro multiplication protocol for Curcuma mangga : Studies on carbon, cytokinin source and explant size - Waman, A A; Bohra, P; Karthika Devi, R; Pixy, J (Journal of Horticultural Sciences, 2021)
Mango ginger (Curcuma mangga Valeton & Zijp.) is an underutilized rhizomatous species that has been valued in tropical Asian countries as a source of vegetable, spice, salad, medicine, and essential oil. This species is hardy and requires less care for obtaining good yields. Rhizomes are the commonly used propagules for the species, which are also the economic part of the crop. Huge quantity of seed rhizomes is required to promote this crop in larger areas. An efficient in vitro multiplication protocol is one of the options to meet the planting material requirement. Effects of carbon source (glucose, fructose and sucrose) and concentration (1 and 3%, w/v), cytokinins (BAP and meta topolin) and concentration (1 mg/L and 2 mg/L), size of explants (one/ two/ three bud) and IBA treatment (0, 250, 500 and 1,000 mg/L) for concurrent ex vitro rooting cum hardening were studied. Results revealed that for facilitating efficient multiplication, the medium should be supplemented with glucose (3%) as a carbon source and meta topolin (1 mg/L) as cytokinin. Two-bud explant should be used for subculture as it promoted superior shoot proliferation. Concurrent ex vitro rooting cum hardening was possible even without auxin treatment. The present protocol could be useful for large-scale production of quality planting material of this underexploited tropical species.
Keywords: Ex vitro rooting; Glucose; Hardening; Inoculum size; Mango ginger; Tropical